Post-divorce Adjustment: An Assessment of a Group Intervention - Lee, James M.; Hett, Geoffrey G. (Canadian Journal of Counselling and Psychotherapy, 2011)
The present study examined the effects of a group intervention program designed to teach coping skills to recently separated and divorced adults. Twenty-four participants were randomly assigned to a program group (n = 12) and a wait list control group (n = 12) and were administered the Personal Orientation Inventory, the State-Trait Anxiety Inventory, and the Beck Depression Inventory. The experimental group began an eight session program designed to help group members deal with post-divorce trauma. Each session included an opportunity for individuals to present specific difficulties or issues. Topics covered in the sessions included: stress management, stages of uncoupling, communication skills, relationships with ex-spouses, relatives and friends, legal issues, children and divorce, loneliness and depression, dating and sexuality. Overall results indicated that the intervention program promoted reduced depression and anxiety, greater ability to live in the present, greater independence, more spontaneity, and an increase in the experimental subjects' ability to form meaningful relationships.